2010
DOI: 10.1108/18347641011048101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the types of NAS provisions and gifts hospitality on auditor independence

Abstract: PurposeAuditor independence is regarded as the cornerstone in the auditing profession. But there is lack of research to examine the influence of the types of non‐audit services provisions and gift hospitality on auditor independence. This paper aims to fill this gap.Design/methodology/approachThis Hong Kong study differs significantly from prior studies and is the first to examine the perceived independence by encompassing both qualitative and quantitative analysis. Binary logistic regression is used to captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(79 reference statements)
1
12
0
Order By: Relevance
“…Moreover, our research gives the evidence for the positive impact of supplying taxation services on auditor independence in Vietnam and the same trend is also found in research of Law (2010) in Hong Kong. When compared to findings of Le (2017) with the same research environment, which shows taxation services deteriorate auditor independence, our research results show the converse, paving the way for another perspective on this relationship.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, our research gives the evidence for the positive impact of supplying taxation services on auditor independence in Vietnam and the same trend is also found in research of Law (2010) in Hong Kong. When compared to findings of Le (2017) with the same research environment, which shows taxation services deteriorate auditor independence, our research results show the converse, paving the way for another perspective on this relationship.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to management advisory services and taxation services, Law (2010) showed that the provision of internal audit services also influenced auditor independence. The foregoing discussion and rationale leads to the following hypotheses:…”
Section: The Effect Of Non-audit Services (Nas) On Auditor Independencementioning
confidence: 99%
“…The rationale for using Big 4 auditors in our study is that Big 4 auditors can more easily relocate within the same firm or to other accounting firms in other countries. Big 4 accounting firms have been expanding their practices to include a wide array of audit and non‐audit services in their businesses (Law, , , ). In addition, Big 4 auditors audit most of the large multinational companies (Shafer, Morris & Ketchand, ), so the opportunity to relocate for Big 4 auditors is higher (Law, ).…”
Section: Methodsmentioning
confidence: 99%
“…This is justified given that valuable gifts can be considered a type of fee provided in an indirect form and, as mentioned above, income is the main factor affecting auditors' independence. Nevertheless, Law (2010) concluded that the offer of valuable gifts does not affect auditors' independence, this being a practice common in the Chinese culture where the research was held, however, this is not the case in Greece.…”
Section: 7139mentioning
confidence: 99%